Peri-Implant Inflammation in Waterpipe Users and Cigarette Smokers: An Observational Study - Dena Ali; Qumasha M. Al-Yahya; Jagan Kumar Baskaradoss (Elsevier, 2023)
ABSTRACT: Objective: The aim of this study was to compare peri-implant clinical and radiographic status and levels of advanced glycation endproducts (AGEs) in peri-implant sulcular fluid (PISF) in waterpipe users and cigarette smokers. Methods: Waterpipe users, cigarette smokers, and never smokers were included. Demographic details were collected using a questionnaire. Characteristics of implants (dimensions, jaw location, depth of placement, insertion torque, and duration in function) were recorded. Peri-implant modified plaque and gingival indices (mPI and mGI), probing depth (PD), and crestal bone loss (CBL) were recorded in all groups. Volume of PISF and levels of AGEs were determined using standard techniques. Sample-size estimation was done on data from a pilot investigation, and correlation between clinicoradiographic and immunoinflammatory parameters was assessed using logistic regression models. Probability values <.05 were considered statistically significant. Results: In all, 25, 25, and 24 cigarette smokers, never smokers, and waterpipe users, respectively, were examined. All participants were male and had comparable mean ages. Cigarette smokers and waterpipe users had a smoking history of 20.2 ± 3.5 years and 18.8 ± 0.6 years, respectively. The mPI (P < .01), CBL (P < .01), PD (P < 0.01), and mGI (P < .01) were significantly higher in cigarette smokers and waterpipe users than never smokers. There was no significant difference in clinicoradiographic status and AGE concentrations in waterpipe users and cigarette smokers. A statistically significant correlation was recorded between AGEs and PD in cigarette smokers (P < .01) and waterpipe users (P < .01). Conclusions: Waterpipe usage is not less hazardous to peri-implant tissue health than conventional cigarette smoking. It is imperative to caution patients with dental implants about the detrimental effects of tobacco products on oral health.